PENGGUNAAN WEIGHTED PRODUCT (WP) DAN ELIMINATION ET CHOIX TRANDUSIANT LA REALITÉ (ELECTRE) DALAM MENENTUKAN TEMPAT BERBELANJA KEBUTUHAN RUMAH TANGGA TERFAVORIT BERBASIS GUI MATLAB (Studi Kasus : Ritel Modern di Kota Surakarta) - Syavhana Yusricha Zuhri Putri; Sudarno Sudarno; Tatik Widiharih (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2017)
Surakarta is one of the fastest growing cities. One of them is marked by many shopping places to fulfill household needs. This causes competition between shopping places. Based on these conditions, a method is needed to assess the customer's favorite shopping place to create a shopping place that matches the customer's expectations. Methods that can be applied to choose the most favorite shopping place are WP and ELECTRE. These two methods can make a decision to get a favorite alternative based on certain criteria in solving Multi Attribute Decision Making (MADM) problems. There are eight alternatives and thirteen criterias. The alternatives are Indomaret Point, Alfamidi, Superindo, Lotte Mart, Hypermart, Carrefour, Luwes Group and Goro Assalam. While the criterias are price of goods, service, stock of goods, arrangement of goods, hygiene, location, ease of transaction, facility, employee appearance, place comfort, employee friendliness, security, and courtesy of employee. The result of this study shows that the favorite type of shopping place for household needs according to WP and ELECTRE method is Carrefour. This study also produces a GUI Matlab programming application that can help users in performing data processing.Keyword : MADM, WP, ELECTRE, Shopping place, GUI Matlab